IMPACT OF DITCHING IN A SMALL FORESTED CATCHMENT ON CONCENTRATIONS OF SUSPENDED MATERIAL, ORGANIC CARBON, HYDROGEN IONS AND METALS IN STREAM WATER - Astrom M.; Aaltonen E.K.; Koivusaari Ju. (My University, 2001)
Stream-water samples were collected during a 4-year-period in two small streams, one whose catchment was ditched for forestry halfway through the sampling period and another nearby reference stream whose catchment was not ditched during this period. The main aim was to study the impact of forest ditching on stream-water quality. Whereas the artificial drainage did not change the hydrograph pattern, it had a large effect on stream hydrochemistry: the concentrations of suspended material, Mn, Ca, Mg and Al increased, the concentrations of total organic carbon decreased, and pH increased by approximately one unit, from an average of 4.4 to 5.4. The increase in suspended material, Mn and Al concentrations is explained by the physical mobilisation of mineral particulates/colloids from mineral soils (till) exposed on the ditch slopes beneath the peat layer, while the increase in Ca and Mg loads is explained by the release of Ca2+ and Mg2+ in exchange reactions in this same soil layer. The increase in pH and decrease in TOC concentrations after ditching are related to changes in hydrological flow paths in the catchments, and most likely to immobilisation of both hydrogen ions and humic substances in the near neutral till horizon exposed beneath the peat layer. Only the aquatic abundance of Fe was not significantly affected by the ditching.
Keywords: STREAM; HYDROCHEMISTRY; DITCHING; LEACHING; CATCHMENT; ARTIFICIAL DRAINAGE